2020
DOI: 10.1609/aaai.v34i05.6197
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of Opinion Diffusion is PSPACE-Complete

Abstract: We analyse opinion diffusion in social networks, where a finite set of individuals is connected in a directed graph and each simultaneously changes their opinion to that of the majority of their influencers. We study the algorithmic properties of the fixed-point behaviour of such networks, showing that the problem of establishing whether individuals converge to stable opinions is PSPACE-complete.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Which rules converge to a stable state? (Section 4) While some works consider convergence of diffusion processes under simultaneous updates of the agents [18,26,11], we focus on sequential updates. For the case of only two opinions a standard update rule is to follow the (strict) majority of the neighbours' opinions.…”
Section: Rulementioning
confidence: 99%
“…Which rules converge to a stable state? (Section 4) While some works consider convergence of diffusion processes under simultaneous updates of the agents [18,26,11], we focus on sequential updates. For the case of only two opinions a standard update rule is to follow the (strict) majority of the neighbours' opinions.…”
Section: Rulementioning
confidence: 99%
“…It was proven in [27] that periodicity is always one or two. Recently, it was shown in [15] and [52] that it is PSPACE-complete to decide whether the periodicity is one or not for a given coloring of a directed graph. Regarding the stabilization time, Fogelman, Goles, and Weisbuch [21] showed that it is bounded by O n 2 .…”
Section: Related Workmentioning
confidence: 99%
“…Particularly, the majority-based models, where each node chooses the most frequent color among its neighbors, have received a substantial amount of attention, cf. [15]. This imitating behavior can be explained in several ways: an agent that sees a majority agreeing on an opinion might think that her neighbors have access to some information unknown to her and hence they have made the better choice; also agents can directly benefit from adopting the same behavior as their friends (e.g., prices going down).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, when voters update their preferences looking at their connections, it is the strategic positioning of a party's electorate that matters, rather than the initial majority (what they call information gerrymandering). Undoubtedly, a metric that allows us to forego the equilibrium computation of a highly complex system is an important practical tool, significantly simplifying the analysis of the opinion diffusion dynamics, a notoriously complex problem [16,17,18]. Moreover, it allows for a further understanding of the effects of manipulation, for example through the strategical placements of bots or zealots to alter the network dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Research on this has been both empirical [34] and theoretical [35,36,10] (see overviews [37,38]), including attempts to find influential nodes in the social graph [39]. Computational models of opinion diffusion have looked at the fixedpoint properties of the graph dynamics, in connection with consensus formation [17] and its complexity [18]. An important stream of research has looked at how to control opinion diffusion by external intervention, for example through bribery [13], false-name attacks [40] or information control [11], and we see our results as introducing effective heuristics for outcome prediction in those frameworks.…”
Section: Introductionmentioning
confidence: 99%